Functionalized polyester-based materials as UV curable adhesives. (November 2019) - Cernadas, T.; Santos, M.; Gonçalves, F.A.M.M.; Alves, P.; Correia, T.R.; Correia, I.J.; Ferreira, P.
Graphical abstract: Highlights: Photocrosslinkable PCL based macromers were synthesized by functionalization with Laromer® 9000; The macromers were crosslinked via UV irradiation using Irgacure® 2959 as the photoinitiator; All samples showed to be thrombogenic and non-haemolytic; Higher crosslinking degrees had a positive impact on the biocompatibility. Abstract: UV curable adhesives offer major advantages in comparison to other polymeric based adhesive systems, such as fast-curing rate and control of the polymerization heat evolution, being ideal for application on damaged tissues. Herein, functionalized polymers were prepared by modifying polycaprolactone diol (PCL) with an isocyanate-functional unsaturated acrylic ester, Laromer® 9000, using two different proportions. These functionalized materials were chemically/physically characterized and, after the addition of a biocompatible photoinitiator (Irgacure® 2959), were crosslinked by UV light irradiation. Such procedure allows the obtention of flexible transparent films. Films' properties such as swelling, hydrolytic degradation, thermal stability, surface energy and adhesive capacity were evaluated. Furthermore, to assess the applicability of the films in biomedical applications, their haemocompatibility and biocompatibility were determined using human dermal fibroblasts as model.